Statistical Modeling on Blindness and Visual Impairment Data - Khanal, Shankar Prasad; Acharya, Krishna Prasad; Uprety, Pravat; Shah, Santosh Kumar (Journal of Institute of Science and Technology, 2015)
Blindness and visual impairment remain leading causes of disability in the world, and also considered one of the major eye problems in Nepal. This study was planned to identify the significant risk factors of visual impairment and blindness based on hospital data. The analysis is based on 2000 patients’ information with age ?40 years retrospectively. Logistic regression model is used to identify the risk factors of visual impairment. Altogether 710(36%) subjects were having visually impaired (low vision) and very few 29(1.45%) were having blindness. The proportion of having visual impairment and blindness each is found higher in the females as compared to males( p = 0.026). The prevalence of having visual impairment in the age group of 40 - 49 years with 95% C.I. is 13.11 %( 10.76% - 15.75%) and it reaches to very high (89.00%; 84.89% - 92.30%) in the patients having age 70 years or more. The odds of having visual impairment is 8 times more(OR = 7.99, 95% C.I.: 3.99 - 15.98, p < 0.001) in 60 - 69 age group of people as compared with those of 40 - 49 age group based on visual acuity after correction. Risk of developing visual impairment is found to be increasing exponentially with increasing age. Journal of Institute of Science and Technology, 2014, 19(1): 1-6